A Theoretical Investigation of Two Typical Two‐Photon pH Fluorescent Probes. (17th December 2012) - Xu, Zhong; Ren, Ai‐Min; Guo, Jing‐Fu; Liu, Xiao‐Ting; Huang, Shuang; Feng, Ji‐Kang
Abstract Intracellular pH plays an important role in many cellular events, such as cell growth, endocytosis, cell adhesion and so on. Some pH fluorescent probes have been reported, but most of them are one‐photon fluorescent probes, studies about two‐photon fluorescent probes are very rare. In this work, the geometrical structure, electronic structure and one‐photon properties of a series of two‐photon pH fluorescent probes have been theoretically studied by using density functional theory (DFT) method. Their two‐photon absorption (TPA) properties are calculated using the method of ZINDO/sum‐over‐states method. Two types of two‐photon pH fluorescent probes have been investigated by theoretical methods. The mechanisms of the Photoinduced Charge Transfer (PCT) probes and the Photoinduced Electron Transfer (PET) probes are verified specifically. Some designed strategies of good two‐photon pH fluorescent probes are suggested on the basis of the investigated results of two mechanisms. For the PCT probes, substituting a stronger electron‐donating group for the terminal methoxyl group is an advisable choice to increase the TPA cross section. For the PET probes, the TPA cross sections increase upon protonation.